2023
DOI: 10.1093/inthealth/ihad003
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the well-being of people affected by skin NTDs in Kaduna and Kwara States, Nigeria: a photovoice and scoping review study

Abstract: People affected by skin neglected tropical diseases (NTDs) grapple with both physical and emotional reactions that compromise their health and well-being. Multiple studies with people affected by skin NTDs have shown high levels of poor mental well-being using self-report questionnaires or psychological measures. However, few have provided in-depth documentation of lived experiences from the perspective of affected persons and there is limited consideration of how their viewpoints can be used to shape interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Self-isolation was a coping strategy by BU participants in this study and this is consistent with studies of HIV, leprosy and cutaneous leishmaniasis [ 54 56 ]. However, avoidance strategies are commonly associated with low self-esteem, increased levels of anxiety, depression, reduced quality of life, impaired psychological and mental well-being and suicidal ideation [ 41 , 57 ]. Consistent with this, individuals with severe disease in the current study who used self-isolation for coping, reported an increased psychosocial burden, including worry, sadness and distraction in school.…”
Section: Discussionmentioning
confidence: 99%
“…Self-isolation was a coping strategy by BU participants in this study and this is consistent with studies of HIV, leprosy and cutaneous leishmaniasis [ 54 56 ]. However, avoidance strategies are commonly associated with low self-esteem, increased levels of anxiety, depression, reduced quality of life, impaired psychological and mental well-being and suicidal ideation [ 41 , 57 ]. Consistent with this, individuals with severe disease in the current study who used self-isolation for coping, reported an increased psychosocial burden, including worry, sadness and distraction in school.…”
Section: Discussionmentioning
confidence: 99%